Pancreatic duct fluid culture in patients with chronic pancreatitis undergoing operative intervention and its implications on post operative course - Krishna, Sai P.; Somasekar, R. D. R.; A., Sivasankar; B., Kesavan; Chidambaram, Pon M.; Ramamurthy, C. (International Surgery Journal, 2021)
Background: The role of bacteria in pathogenesis of chronic pancreatitis is poorly understood. Our aim was to analyse pancreatic duct fluid culture in patients undergoing operative intervention for chronic pancreatitis and its implications in post operative outcomes. Methods: Among 35 patients, 17 underwent Freys, 13 underwent longitudinal pancreatico-jejunostomy, 5 underwent cystojejunostomy. Duct fluid culture was obtained intraoperatively and analysed and compared with preoperative parameters and post operative outcomes. Results: 20 patients had positive duct fluid culture. Most common pathogen isolated was Klebsiella (8 patients). The only preoperative parameter which showed significant association was fasting blood glucose level. Wound infections were seen in 11 of which 10 had positive duct culture, out of which 9 had the same organism of that in duct culture. Mean hospital stay was 9±1.07 and 10±1.13 days in patients without and with infectious complications respectively. Conclusions: Older concept of sterile PD fluid in patients with CP may no longer hold true. In our study upto 60% of patients showed positive PD culture. By starting appropriate antibiotic we can reduce the length of hospital stay in patients who have septic complications. However large centre studies may guide us further into the importance of this concept and the role of bacteria in the pathogenesis of CP.